Which of the following is equation of a line that passes through (-2,1) and (-4,-3)?
Answer:
y = 2x + 5Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
=======================================
We have the points (-2, 1) and (-4, -3). Substitute:
[tex]m=\dfrac{-3-1}{-4-(-2)}=\dfrac{-4}{-2}=2[/tex]
[tex]y=2x+b[/tex]
Put the coordinates of the point (-2, 1) to the equation:
[tex]1=2(-2)+b[/tex]
[tex]1=-4+b[/tex] add 4 to both sides
[tex]5=b\to b=5[/tex]
Finally:
[tex]y=2x+5[/tex]
Given: m∠AEB = 45°
∠AEC is a right angle.
Prove: bisects ∠AEC.
Proof:
We are given that m∠AEB = 45° and ∠AEC is a right angle. The measure of ∠AEC is 90° by the definition of a right angle. Applying the gives m∠AEB + m∠BEC = m∠AEC. Applying the substitution property gives 45° + m∠BEC = 90°. The subtraction property can be used to find m∠BEC = 45°, so ∠BEC ≅ ∠AEB because they have the same measure. Since divides ∠AEC into two congruent angles, it is the angle bisector.
The segment bisects \AEC because \AEB and \BEC are both 45\u00b0, proven using the Angle Addition Postulate and the Subtraction Property of equality.
Explanation:To prove that the segment bisects \AEC, begin by acknowledging the given information that m\AEB = 45\u00b0 and \AEC is a right angle with a measure of 90\u00b0. According to the Angle Addition Postulate, m\AEB + m\BEC = m\AEC. Substitute the known values to get 45\u00b0 + m\BEC = 90\u00b0. Utilizing the Subtraction Property of equality allows us to solve for m\BEC, finding it to also be 45\u00b0. This means that \BEC ≅ \AEB which leads us to conclude that since they have equal measures, the segment indeed bisects \AEC.
What is the measure of the radius of circle m? see picture
Answer:
10.5 units
Step-by-step explanation:
Since M is the centre of the circle. The measure to the edge is the radius.
Which in this case is 10.5 units
Answer: A. 10.5 units
Step-by-step explanation: The answer would be 10.5 units because the radius is equal to half the circle. MS is a radius, and MR is a radius. A radius has one point in the center, and one point on the circle.
does the point (3,-1) lie on the circle (x+1)^2 + (y-1)^2=16
Answer:
No.
Step-by-step explanation:
The circle of that equation lies on the point (3,1) as its furthest point to the right (x-axis) and therefore could never also lie on the point (3,-1).
Your equation is in center radius form, which is as follows:
[tex](x-h)^2+(y-k)^2=r^2[/tex]
Noting that your radius is 4 (since your radius squared is 16).
To graph your circle, simply go to your origin (h, k) which in this case is (-1, 1) and then count out in any direction (up, down, left, or right -- no diagonals) 4 units (since your radius is 4). This will give you the four outermost edges of your circle. Simply fill in the gaps from there, and you'll have sketched your circle.
No. The circle of that equation lies on the point (3,1) as its furthest point to the right (x-axis) and thus could never lie on the point (3,-1).
What is a circle?A circle is a shape consisting of all points in a plane that are given the same distance from a given point called the center.
The equation is in center radius form, which is as follows:
(x - h)² + (y - k)² = r²
the radius is 4 (since your radius squared is 16).
Substituting 3 for x and -1 for y:
(3 + 1)^2 + (-1 - 1)^2 = 16
4^2 + (-2)^2 = 16
16 + 4 = 16
20 = 16
Hence, we can see 20 is clearly not equal to 16, so we know the point (3, -1) can’t lie on that circle.
Learn more about circle here;
brainly.com/question/12512221
#SPJ3
The altitude of an isosceles triangle is the same segment in the triangle as
the
A. hypotenuse
B. median
c. bisector
D. leg
B -median
Hypotenuse is only right triangles and legs are sides of a triangle. A bisector divides something in half evenly . Altitude is height of a triangle and median is the same segment
:
The altitude of an isosceles triangle is the same segment in the triangle as the bisector.
What is a bisector?The bisector is a line that divides a line or an angle into two equivalent parts. The bisector of a segment always contains the midpoint of the segment.
In an isosceles triangle,
Bisector of vertex angle = midline of base side = altitude
The altitude of an isosceles triangle is the same segment in the triangle as the bisector.
Option C is correct.
Find out more information about bisector here
https://brainly.com/question/13880193
#SPJ2
Find the slope of the line that passes through the points (-2,3) and (2,7)
Answer:
[tex]\large\boxed{\frac{1}{1}\,\text{or}\,1}[/tex]
Step-by-step explanation:
In this question, we're trying to find the slope with the given points.
To find the slope, we're going to need to sue the slope formula.
Slope formula:
[tex]\text{Slope}=\frac{y2-y1}{x2-x1}[/tex]
You would plug in the coordinates to its right spot.
Plug in -2 to x1, 3 in y1, 2 in x2, and 7 in y2.
Your equation should look like this:
[tex]\text{Slope}=\frac{7-3}{2-(-2)}[/tex]
Now, you will solve:
[tex]\text{Slope}=\frac{7-3}{2-(-2)}\\\\\text{Slope}=\frac{4}{2-(-2)}\\\\\text{Carry the minus sign over to the -2, turning it to a positive 2}\\\\\text{Slope}=\frac{4}{2+2}\\\\\text{Slope}=\frac{4}{4}\\\\\text{Divide}\\\\\text{Slope}=\frac{1}{1}=1[/tex]
When you're done solving, you should get 1.
This means that the slope of the line is 1/1 or 1
I hope this helped you out.Good luck on your academics.Have a fantastic day!Finding the slope using two points:
The formula for slope is
[tex]\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
In this case...
[tex]y_{2} =7\\y_{1} =3\\x_{2} =2\\x_{1} =-2[/tex]
^^^Plug these numbers into the formula for slope...
[tex]\frac{7-3}{2 - (-2)}[/tex]
[tex]\frac{4}{4}[/tex]
^^^This can be further simplified down to...
1
^^^This is your slope
Hope this helped!
~Just a girl in love with Shawn Mendes
Piecewise defined function.
f(x) = {-x^2+2x+2 if
[tex]x \leqslant - 5[/tex]
{-3/4x+3 if
[tex]x > 1[/tex]
find what f(-5) =
Answer:
f(-5) = -33
Step-by-step explanation:
f(x) = {-x^2+2x+2 if x ≤ - 5
{-3/4x+3 if x > 1
find what f(-5) =
If x=-5, we use the first equation
f(-5) = -x^2+2x+2 since it has the equal to part
= - (-5)^2 +2(-5) +2
= -25 -10+2
= -35+2
=-33
A football coach is trying to decide: when a team ahead late in the game, which strategy is better?
A)
B)
C)
or D)
APEX
Answer: B
Step-by-step explanation:
richard cuts a peice of wood for a project the first cut is shown and can be represented by the equation y=1/2x+2 the second cut need to be parellel to the first it will pass through the point (0,-7) identify the equation that represents richards second cut
Answer:
B)
Step-by-step explanation:
First, lets try to build the second equation, it has the general shape
[tex]y=m *x+b[/tex]
Where b is a constant (a number) and m the slope, another constant.
Using the given condition (0,-7) you can find the first constant of our second equation, just put "0" where you see "x", and put -7 where there is a "y".
That gives us that b is equals to -7.
Now we only need to know that the condition for 2 linear equations to be parallels is that their slope have to be the same or multiple between each others, this means that "m" of our second equation has to be equal to 1/2
thus, our second equation is [tex]y=\frac{1}{2}*x-7[/tex]
Another way to see this is that you can compare two linear equations y1=m1*x1 + b1, and y2=m2*x2+b2, if these two intersect in somewhere, this condition should meet:
X= (b1-b2)/(m2-m1).
If the slopes are the same, the above equation gives us an error, meaning that the linear equations are, in fact parallels.
Graph the functions on the same coordinate axis. {f(x)=−2x+1g(x)=x2−2x−3
What are the solutions to the system of equations?
select each answer
(2, 3)
(−2, 5)
(2, −3)
(2, 5)
(−2, −3)
Answer:
(2,-3) and (-2,5)
Step-by-step explanation:
Let us graph the two equations one by one.
1. [tex]f(x)=-2x+1[/tex]
If we compare this equation with the slope intercept form of a line which is given as
[tex]y=mx+c[/tex]
we see that m = -1 and c =1
Hence the slope of the line is -2 and the y intercept is 1. Hence one point through which it is passing is (0,1) .
Let us find another point by putting x = 1 and solving it for y
[tex]y=-2(1)+1[/tex]
[tex]y=-2+1 = -1[/tex]
Let us find another point by putting x = 2 and solving it for y
[tex]y=-2(2)+1[/tex]
[tex]y=-4+1 = -3[/tex]
Hence the another point will be (2,-3)
Let us find another point by putting x = -2 and solving it for y
[tex]y=-2(-2)+1[/tex]
[tex]y=+1 = 5[/tex]
Hence the another point will be (-2,5)
Now we have two points (0,1) ,(1,-1) , (2,-3) and (-2,5) we joint them on line to obtain our line
2.
[tex]g(x)=y=x^2-2x-3[/tex]
[tex]y=x^2-2x+1-1-3[/tex]
[tex]y=(x-1)^2-4[/tex]
[tex](y+4)=(x-1)^2[/tex]
It represents the parabola opening upward with vertices (1,-4)
Let us mark few coordinates so that we may graph the parabola.
i) x=0 ; [tex]y=y=(0)^2-2(0)-3=0-0-3=-3[/tex] ; (0,-3)
ii)x=-1 ; [tex]y=(-1)^2-2(-1)-3=1+2-3=0[/tex] ; (-1,0)
iii) x=2 ; [tex]y=(2)^2-2(2)-3 = 4-4-3 =-3[/tex] ;(2,-3)
iii) x=1 ; [tex]y=(1)^2-2(1)-3 = 1-2-3 =-4[/tex] ;(1,-4)
iii) x=-2 ; [tex]y=(-2)^2-2(-2)-3 = 4+4-3 =5[/tex] ;(-2,5)
Now we plot them on coordinate axis and line them to form our parabola
When we plot them we see that we have two coordinates (2,-3) and (-2,5) are common , on which our graphs are intersecting. These coordinates are solution to the two graphs.
Answer:
so you dont have to suffer lol heres a screenshot
Step-by-step explanation:
Martina begins a dive at sea level. She dives down 20 feet, and then rises 7 feet.
She dives again, going down 9 more feet. How far below sea level is Martina?
Answer:
22 feet below sea level
Step-by-step explanation:
If she goes down by 20 and back up by 7 the overall effect is going down by 13 and then going down 9 more feet makes it a total of 22 feet.
Answer:22
Step-by-step explanation:
-20+7-9= -22 ft, or 22 ft below sea level
Please help me, I Am getting-28 but I do t think it is correct
Answer:
-28
Step-by-step explanation:
[tex]-(2-2^3)^2-4 \cdot (-2)[/tex]
We going to use PE(MD)(AS).
So P means ( ).
We do have operations to perform in the ( ).
We have [tex]2-2^3[/tex] in the first set of ( ) and (-2) in the second set of ( ).
There are no operations in the second set containing -2.
So we are just focusing on the [tex]2-2^3[/tex] right now.
You have subtract and exponent here.
Exponents come first in PE(MD)(AS) so we will perform that first.
[tex]2-2^3=2-8=-6[/tex]
Let's go back to the original problem now.
[tex]-(2-2^3)^2-4 \cdot (-2)[/tex]
[tex]-(-6)^2-4 \cdot(-2)[/tex]
Now there are no longer any operations grouped together by use of ( ).
It on to the rest of PE(MD)(AS).
So now we are doing the E part, the exponents.
[tex]-(36)-4 \cdot(-2)[/tex]
Now there is multiplication and subtraction left.
(MD) comes before (AS) so we do the multiplication and then the subtraction. So I'm going to do 4(-2) now:
[tex]-(36)-(-8)[/tex]
Subtraction is addition of the opposite so you could write:
[tex]-(36)+8[/tex]
We don't really need ( ) around the first number:
[tex]-36+8[/tex]
36-8 is 28 but since 36>8 and 36 has a negative sign on it, the answer is -28.
Do you guys know the answer for number 4
Answer:
G !!! Have a good day BLOODY
You graph the function f(x)=-|×|-12
in the
standard viewing window of -10 to 10. Will you be
able to see the graph? Explain.
Answer:
See attachment
Step-by-step explanation:
We want to graph [tex]f(x)=|x|-12[/tex] on the interval -10 to 10.
Let [tex]g(x)=|x|[/tex] be the parent absolute value function.
We can easily graph [tex]f(x)=|x|-12[/tex], if we use translation.
When the parent function is shifted downwards by 12 units, we obtain the graph of [tex]f(x)=|x|-12[/tex].
The parent function is a v-shaped graph with vertex at the origin.
We shift the parent function down so that its vertex is now at (0,-12) to get the graph of [tex]f(x)=|x|-12[/tex] .
See attachment for the graph of [tex]f(x)=|x|-12[/tex] on the specified interval.
Answer:
Which of the following did you include in your response?
No, you will not see the graph.
When x is 0, y is –12, which is outside the viewing window.
Because the function has been reflected, it opens down.
From x = –10 to x =10, the y-values range from –22 to –12.
Step-by-step explanation:
Write (1/3i)-(-6+2/3i) as a complex number in standard form
Answer:
[tex]6+\frac{i}{3}[/tex]
Step-by-step explanation:
[tex]\frac{1}{3\imath}-(-6+\frac{2}{3\imath})[/tex]
[tex]\frac{1}{3\imath}+6-\frac{2}{3\imath}[/tex]
taking like terms together
[tex]\frac{1}{3\imath}-\frac{2}{3\imath}+6[/tex]
taking LCM
[tex]\frac{1-2}{3\imath}+6[/tex]
[tex]\frac{-1}{3\imath}+6[/tex]
taking LCM
[tex]\frac{-1+18\imath}{3\imath}[/tex]
splitting the term
[tex]\frac{-1+18\imath}{3\imath}[/tex]
splitting the term
[tex]-\frac{1}{3\imath}+\frac{18\imath}{3\imath}[/tex]
[tex]-\frac{1\times3\imath}{3\imath \times \imath}+6[/tex]
[tex]-\frac{i}{3\imath^2}+6[/tex]
we know that
[tex]\imath^2=-1[/tex]
putting this value in above equation
[tex]\frac{\imath}{3}+6[/tex]
Simplify the following algebraic expression: 6(2y + 8) - 2(3y - 2)
Answer:
[tex]\large\boxed{6y+52}[/tex]
Step-by-step explanation:
In this question, we're going to simplify the expression.
We would do this by distributing and solving after.
Solve:
[tex]6(2y + 8) - 2(3y - 2)\\\\\text{Distribute the 6 to the 2y and 8}\\\\12y+48- 2(3y - 2)\\\\\text{Distribute the -2 to the 3y and -2}\\\\12y+48-6y+4\\\\\text{Combine like terms}\\\\6y+48+4\\\\\boxed{6y+52}[/tex]
When you're done solving, you should get 6y+52
This means that the simplified version would be 6y+52
I hope this helped you out.Good luck on your academics.Have a fantastic day!The reciprocal of -7 is: -7 7 -1/7 1/7
Answer: -1/7
Step-by-step explanation: The reciprocal of -7 is -1/7. Flip -7 to get the answer. -7 is the same as -7/1, so flip the numbers to find the reciprocal.
Help me on this math question
Answer: A. 1.55 repeating.
Step-by-step explanation: Since 5/9 is not going to end as .5, the answer would be 1.55 repeating. 5/10 would make the answer be 1.5.
The mixed fraction number 1 5/9 is equal to the decimal number 1.55.... Then the correct option is A.
What is Algebra?Algebra is the study of algebraic expressions, while logic is the manipulation of those concepts.
The decimal number is the sum of a whole number and part of a fraction number. The fraction number is greater than zero but less than one.
The mixed fraction number is given below.
⇒ 1 5/9
Convert the mixed fraction number into the fraction number. Then we have
1 5/9 = 14 / 9
Convert the fraction number into a decimal number, then we have
⇒ 14/9
⇒ 1.55......
The mixed fraction number 1 5/9 is equal to the decimal number 1.55.... Then the correct option is A.
More about the Algebra link is given below.
https://brainly.com/question/953809
#SPJ2
Find the number of the different ways, for 3 students to sit on 7 seats in one row.
a. 840
b. 35
c. 210
d. 30
Answer:
210
Step-by-step explanation:
Here comes the problem from Combination.
We are being asked to find the number of ways out in which 3 students may sit on 7 seats in a row. Please see that in this case the even can not be repeated.
Let us start with the student one. For him all the 7 seats are available to sit. Hence number of ways for him to sit = 7
Let us see the student second. For him there are only 6 seats available to sit as one seat has already been occupied. Hence number of ways for him to sit = 6
Let us see the student third. For him there are only 5 seats available to sit as two seat has already been occupied. Hence number of ways for him to sit = 5
Hence the total number of ways for three students to be seated will be
7 x 6 x 5
=210
graph the line with slope -2/3 passing through the point (-3,5)
Answer:
[tex]\large\boxed{y-5=-\dfrac{2}{3}(x+3)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
(x₁, y₁) - point on a line
We have the slope [tex]m=-\dfrac{2}{3}[/tex] and the point [tex](-3,\ 5)[/tex].
Substitute:
[tex]y-5=-\dfrac{2}{3}(x-(-3))\\\\y-5=-\dfrac{2}{3}(x+3)[/tex]
can someone help with this question?
Answer:
y ≤ ¼x + 1
Step-by-step explanation:
Starting from the y-intercept of course, use rise\run until you hit another endpoint [finding the rate of change (slope)]. That means me we go up north one block, then go over four blocks east, and since the slope is already simplified, we do not need to go any further. Now all we have left is to determine the correct inequality symbol, and since we know that the bottom portion of the graph is shared, we automatically know it is less than, but to check this, we need to do what is called a zero-interval test [do not recall the actual term], meaning that we plug in 0 for both y and x, getting 0 < 1, which is a GENUINE statement, so the bottom portion stays shaded, otherwise we would have had to shade the top portion if it were a false statement. Finally, we have to determine if we have to add an equivalence line under the inequality symbol, and we DO because as you can see, the line is SOLID BLACK. If it were DASHED BLACK, then it would stay "<" instead of "≤".
I am joyous to assist you anytime.
Determine whether each triangle should be solved by beginning with the Law of Sines or the Law of Cosines. Then solve each triangle. Round measures of sides and angles to the nearest tenth after calculating. a = 8, b = 7, c = 4 Question 3 options: Law of Cosines; A ≈ 89°, B ≈ 61°, C ≈ 30° Law of Sines; A ≈ 89°, B ≈ 61°, C ≈ 30° Law of Sines; A ≈ 30°, B ≈ 61°, C ≈ 89° Law of Cosines; A ≈ 61°, B ≈ 89°, C ≈ 30°
Answer:
Law of Cosines; A ≈ 61°, B ≈ 89°, C ≈ 30°
Step-by-step explanation:
In this problem the given values are the length sides of the triangle, therefore, the triangle should be solved by beginning with the Law of Cosines
step 1
Applying the law of cosines find the value of angle C
we know that
[tex]c^{2}=a^{2}+b^{2}-2(a)(b)cos(C)[/tex]
we have
[tex]a = 8, b = 7, c = 4[/tex]
substitute the values and solve for cos(C)
[tex]4^{2}=8^{2}+7^{2}-2(8)(7)cos(C)[/tex]
[tex]16=64+49-112cos(C)[/tex]
[tex]16=113-112cos(C)[/tex]
[tex]112cos(C)=113-16[/tex]
[tex]cos(C)=97/112[/tex]
[tex]C=arccos(97/112)=30\°[/tex]
step 2
Applying the law of cosines find the value of angle B
we know that
[tex]b^{2}=a^{2}+c^{2}-2(a)(c)cos(B)[/tex]
we have
[tex]a = 8, b = 7, c = 4[/tex]
substitute the values and solve for cos(B)
[tex]7^{2}=8^{2}+4^{2}-2(8)(4)cos(B)[/tex]
[tex]49=64+16-64cos(B)[/tex]
[tex]49=80-64cos(B)[/tex]
[tex]64cos(B)=80-49[/tex]
[tex]cos(B)=31/64[/tex]
[tex]B=arccos(31/64)=61\°[/tex]
step 3
Find the measure of angle A
we know that
The sum of the interior angles of a triangle must be equal to 180 degrees
so
[tex]A+B+C=180\°[/tex]
we have
[tex]C=30\°[/tex]
[tex]B=61\°[/tex]
substitute and solve for A
[tex]A+61\°+30\°=180\°[/tex]
[tex]A+91\°=180\°[/tex]
[tex]A=180\°-91\°=89\°[/tex]
which function represents exponential decay?
a)y=14(0.95)^x
b)y=14(1.95)^x
c)y=14x^1.95
d)y=14/0.95
Answer:
a
Step-by-step explanation:
We are looking for an exponential function [tex]y=a(r)^x[/tex] where r is less than 1.
a works because it is in the form [tex]y=a(r)^x[/tex] where r is less than 1.
b is in the form [tex]y=a(r)^x[/tex] but r is more than 1.
c. and d. are not even exponential functions.
c. is a polynomial
d. is a constant polynomial (no variable)
Find the length of the side labeled x. Round intermediate values to the nearest tenth. Use the rounded values to calculate the next value. Round your final answer to the nearest tenth.
A. 69.4
B. 61.1
C. 57.9
D. 36.9
Answer:
Step-by-step explanation:
Givens
Tan(60) = opposite / adjacent
adjacent = 26
Cos(39) = adjacent / hypotenuse
Solution
Tan(60) = opposite (which is the height) / 26 Multiply both sides by 26
26*tan(60) = opposite Multiply the left.
tan60 = 1.732
26 * 1.732 = opposite
45.033
====================
Cos(39) = adjacent / hypotenuse
cos(39) = 0.7771
0.7771 = 45.0333 / x Multiply both sides by x
0.7771*x = 45.0333 Divide by 0.7771
x = 45.0333 / 0.7771
x = 57.94
Answer:
option C
Step-by-step explanation:
We have to find the value of x
[tex]tan\theta=\frac{perpendicular side}{base}[/tex]
[tex]tan60^{\circ}=\frac{height}{26}[/tex]
We know that [tex] tan60^{\circ}=\sqrt3[/tex]
[tex]\sqrt3=\frac{height}{26}[/tex]
[tex]height=1.732\times 26[/tex]
Where [tex]\sqrt3=1.732[/tex]
Height=45.032
Height=45.0
[tex]cos\theta=\frac{bas}{hypotenuse}[/tex]
[tex] cos 39^{\circ}=\frac{45}{x}[/tex]
[tex]0.777=\frac{45}{x}[/tex]
[tex]x=\frac{45}{0.777}[/tex]
x=57.9
Hence, option C is true.
Which of the following is the equation of a line that passes through (-2,1) and (-4,-3)?
Points [tex]X(-2,1)[/tex] and [tex](-4,-3)[/tex] are defined therefore we have all data we need to construct equation.
Linear function has a form of,
[tex]y=ax+b[/tex]
First calculate the slope a.
[tex]a=\dfrac{dy}{dx}=\dfrac{-3-1}{-4-1}=\dfrac{-4}{-5}=\dfrac{4}{5}[/tex]
Now plug in the coordinates of either one of the points into the linear function. I'll pick point X.
[tex]y=ax+b\Longrightarrow1=\dfrac{4}{5}\cdot(-2)+b[/tex]
Now just solve for b.
[tex]1=-\dfrac{8}{5}+b\Longrightarrow b=\dfrac{13}{5}[/tex]
The equation is therefore,
[tex]\boxed{y=\dfrac{4}{5}x+\dfrac{13}{5}}[/tex]
Hope this helps.
r3t40
What is the volume of a rectangular prism with a length of 2.2 cm, a width of 3.1 cm and a height of 1.2 cm
To find the volume of a rectangular prism, multiply the length by the width by the height.
Volume = 2.2 x 3.1 x 1.2 = 8.184 cm^3
All the dimensions are one decimal place, so if you round the answer to one decimal place it would be 8.2 cm^3
To find the volume of a rectangular prism, multiply the length by the width by the height.Volume = 2.2 x 3.1 x 1.2 = 8.184 cm^3All the dimensions are one decimal place, so if you round the answer to one decimal place it would be 8.2 cm^3
PLEASE HELP!!!
The following table shows a proportional relationship between A and B.
A= 8, 24, 40 B= 3, 9, 15
Write an equation to describe the relationship between A and B.
Answer:
b=3/8a
Step-by-step explanation:
Have a good night/day<3
To find the equation describing the proportional relationship between A and B, we divide B by A and find that the constant of proportionality is 3/8. Thus, the equation is B = (3/8)A.
To find the equation that describes the proportional relationship between A and B, we can start by examining the given pairs of values. For A = 8, B = 3; for A = 24, B = 9; and for A = 40, B = 15. We observe that as A increases, B increases at a constant rate. This suggests a direct proportionality between A and B.
To determine the constant of proportionality (the rate at which B changes with respect to A), we can divide the values of B by the corresponding values of A. Doing so, we find:
B/A for (8, 3) = 3/8B/A for (24, 9) = 9/24B/A for (40, 15) = 15/40All these ratios reduce to 3/8, which is the constant of proportionality. Therefore, B is 3/8 times A, which we can express as:
B = (3/8)A
This equation represents the proportional relationship between A and B, with the constant of proportionality being 3/8.
Simplify this algebraic expression completely.
7x-5(x+6)
Answer:
8x+1
Step-by-step explanation:
Answer:
x=15
Step-by-step explanation:
7x−5(x+6)
=7x+(−5)(x)+(−5)(6)
=7x+−5x+−30
=7x+−5x+−30
=(7x+−5x)+(−30)
=2x+−30
-2x=-30
x=15
Lara is a 50% partner. She is guaranteed payment of no less than 20,000. The partnership's income before deducting guaranteed payment is 50,000 what is Lara's distributive share?
Answer:
Lara's share = 25000
Step-by-step explanation:
Partnership's income = 50,000
Lara's guaranteed payment = 20,000
As the Income 50,000 is larger than Lara's guaranteed payment i.e 20,000. Since Lara is 50% partner so she will receive half the amount of the partnership's income.
Partnership's Income = 50,000
Half of Partnership's income = 50,000/2
= 25,000
Therefore, Lara's distributive share is 25,000.
!!
what is the slope of the line shown below? (4, 8) (2, 4)
Answer:
Slope = 2
Step-by-step explanation:
Slope is the change in y/change in x. So (8-4)/4-2)=2.
Answer: Using the formula below you will get -4/-2 which is slope of 2
Step-by-step explanation:
So you would use the slope formula which is y_{2}- y_{1} / x_{2}-x_{1}